EFFECTIVE MANAGEMENT OF ADMINISTRATIVE PERSONNEL IN UZBEKISTAN’S PUBLIC UNIVERSITIES - Inoyatov, Orzubek (GREEN ECONOMY AND DEVELOPMENT, 2025)
Uzbekistan’s higher education system has rapidly expanded and reformed since 2016, making the effective management of administrative personnel a national priority. This study examines how public universities are improving administrative efficiency amid structural decentralization, financial autonomy, and digital transformation. Despite the growth of institutions and enrollment, legacy bureaucratic models have left many universities with excessive administrative staffing—often exceeding 45–50% of total employees—necessitating reform to enhance economic efficiency and responsiveness. The research identifies a key knowledge gap in understanding how autonomy, human resource (HR) strategies, and digital technologies jointly influence administrative performance in Uzbekistan’s public universities. Using comparative case analysis of Tashkent State University of Economics (TSUE) and Fergana State University, the study evaluates management reforms across three dimensions: economic efficiency, HR modernization, and digital integration. Findings reveal that financial autonomy enables universities to optimize administrative structures and reinvest savings in academic priorities. HR reforms—particularly merit-based recruitment, professional training, and data-driven e-HRM systems—are fostering a more skilled and accountable administrative workforce. Meanwhile, the adoption of Higher Education Management Information Systems (HEMIS) and related digital tools has streamlined workflows and improved transparency, though disparities in digital capacity persist among regional institutions. The results suggest that combining autonomy with targeted HR development and digital governance yields measurable gains in efficiency and service quality. The study concludes that sustained investment in administrative training, equitable digital infrastructure, and data-informed management is essential for building an effective, innovation-driven higher education administration in Uzbekistan.